The Influence of Job Satisfaction and Leadership Style on Work Performance with Work Motivation as an Intervening Variable Study at Bank Syariah Indonesia in Kudus Regency - Alif Aulia Akbar; Kertati Sumekar; Mamik Indaryani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research analyzes the influence of job satisfaction and leadership style on work performance with work motivation as an intervening variable. This research data uses primary data in the form of a questionnaire. The sampling method used purposive sampling and a sample of 120 respondents was obtained. The data analysis used in this research is a structural equation model. The results of this study state that job satisfaction and leadership style have a positive effect on work motivation. The results of this research also state that satisfaction and leadership style do not have a positive effect on work performance. Apart from that, work motivation influences work performance. The results of the mediation test state that work motivation has a greater contribution in mediating the influence of job satisfaction on work performance and work motivation has a greater contribution in mediating the influence of leadership style on work performance.